Processing of metastable beta titanium alloy: Comprehensive study on deformation behaviour and exceptional microstructure variation mechanisms. (1st November 2022) - Zhao, Qinyang; Bolzoni, Leandro; Chen, Yongnan; Xu, Yiku; Torrens, Rob; Yang, Fei
Highlights: TMP-response of PM Ti-5553 alloy in wide parameter range is comprehensively investigated. Typical mechanisms play their role for both α and β phases at different processing domains. Consecutive crystalline rotation and formation of strong fibre texture is found during DDRX. Exceptional and unexcepted evolution mechanisms of α phase are discovered and demonstrated. Precise processing guidance and knowledge extension for deformation mechanism are achieved. Abstract: Thermomechanical processing (TMP) is especially crucial for metastable β titanium alloys, which has received significant attention in the community for a long time. In this contribution, the processing-responding behaviour including microstructure evolution process, texture variation mechanism, and underlying deformation process of powder metallurgy Ti-5553 alloy in a wide processing parameter range was comprehensively investigated. Thermal physical simulation was performed on the alloy at temperatures ranging from 800 °C to 1100 °C, and strain rates between 0.001 s −1 and 10 s −1, to varied deformation degrees of 20%–80% height reduction. It was found that the processing parameters (i.e. temperature, strain rate, and deformation degree) are influential on the deformation process and resultant microstructure. Varied microstructural evolution processes for β phase including flow localization, dynamic recovery, dynamic recrystallization, and grain coarsening are activated in different processing domains, while different evolution mechanisms for α phase including dynamic precipitation, phase separation, dynamic coarsening, and mechanical shearing also play their roles under different processing conditions. In particular, four exceptional evolution mechanisms of α precipitation which have not been previously reported in titanium alloys were discovered and clearly demonstrated, more specifically, they are multi-interior twinning, internal compositing, layered coarsening and selective diffusion-actuated separation. After the establishment of comprehensive microstructural evolution mechanism maps, the guidance for precise processing and the knowledge reserve extension for deformation process of metastable β titanium alloys can be effectively achieved.